Missionaries as Newcomers: A Comparative Study of the Northwest Pacific Coast and Central Australia - Brock, Peggy (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2008)
AbstractMissionaries have generally been treated as a special category of person. Unlike other people who have uprooted and moved to alien lands and societies, they are thought to do so at great personal sacrifice enabling them to spread the Christian word. This paper argues that despite their religious calling missionaries went through similar processes of adjustment as other newcomers who migrated to new lands and societies. The paper analyses the responses of missionaries in two contrasting environments: the northwest Pacific coast, and central Australia. It concludes that the nature of the adjustments missionaries made as newcomers were not determined by their personalities or the policies of the agencies that employed them as much as they were influenced by the societies and environments in which they found themselves. The rhetoric that surrounded nineteenth-century missionary work was premised on an assumption that missionaries were exceptional. A detailed examination of missionary responses to the Pacific northwest of Canada and central Australia reveals that missionaries had much in common with other people who found themselves in new circumstances, among new peoples, and in new places.